Seizure characteristics and the use of anti-epileptic drugs in children and young people with brain tumours and epileptic seizures: analysis of regional paediatric cancer service population - Pilotto, C; Liu, Jo-Fen; Walker, David A.; Whitehouse, William P. (Elsevier, 2018)
PURPOSE: Epileptic seizures complicate the management of childhood brain tumours. There are no published standards for clinical practice concerning risk factors, treatment selection or strategies to withdraw treatment with antiepileptic drugs (AED). METHOD: We undertook a case note review of 120 patients with newly diagnosed brain tumours, referred to a regional paediatric cancer service. RESULTS: Data was available on 117/120 (98%) children <18 years: median age at tumour presentation was 8.1 years (IQR 25°-75°: 3.6-12.7), median follow up was 33 months (IQR 25°-75°: 24-56), and 35/117 (29%) experienced seizures. A cortical tumour location was associated with the highest risk of seizures (OR: 7.1; CI 95% 2.9-17.3). At a median follow up of 24 months (IQR25°-75°: 15-48), 22/35 (63%) with seizures, had a single seizure episode, 15/35 (43%) were seizure free (SF) on AEDs, 13/35 (37%) were SF off AEDs, and 7/35 (20%) experienced continuing epileptic seizures. Overall 34/35 (97%) were treated with AEDs after a seizure, of whom 12/35 (35%) withdrew from AED medication, and although 4/35 (12%) had seizure relapse, all were after further acute events. The median duration of AED before withdrawal was 11 months (IQR25°-75° 5-14 months), and the median follow up after withdrawal was 15 months (IQR25°-75° 5-34 months). CONCLUSIONS: Seizures affect about 1/3rd of children and young people presenting with and being treated for brain tumours particularly when the tumour is in the cerebral cortex. The low risk of recurrent seizures after AED treatment justifies consideration of early withdrawal of AED after seizure control.